Development of an E-Booklet with Emotional Spiritual Quotient (ESQ) Nuances on Virus Material for Class X SMA/MA - Fretty Hengki Karmellia; Lufri Lufri (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2023)
The Merdeka curriculum prioritizes the development of the character profile of Pancasila students through content on learning such as having noble character, piety, critical thinking, working together, and being creative. Based on the observation results, information was obtained that the students' spiritual and emotional abilities needed to be supported through learning biology on viruses. The learning media used before had never contained ESQ nuances in learning media to improve students' spiritual and emotional abilities in the learning process. Students revealed that the existing learning media were less attractive and less motivating to learn and learning media such as printed books, LKPD, and LKS were difficult to carry anywhere, expensive, and easily damaged. So based on these problems, an ESQ nuanced e-booklet was developed on virus material for class X SMA/MA to optimize students' spiritual and emotional abilities. This research uses the 4-D (Four-D) development model consisting of four stages, namely the definition, design, development, and deployment stages, but in the implementation of this research using the Four-D stage only up to the development stage and does not reach the deployment stage because of time constraints and lack of cost in deploying the product commercially. The data in this study were obtained quantitatively descriptive and qualitative. Validation of the e-booklet product was carried out by three validators and practicality tests were carried out on one biology teacher and 35 students of class X MIPA at SMA Pertiwi 1 Padang. The average value obtained from the validity of the e-booklet is 87.22% with very valid criteria. The average value of the e-booklet practicality test is 94.62% with very practical criteria. So, it can be concluded that the e-booklet with ESQ nuances on virus material for class X SMA/MA is very valid and very practical to use as additional biology teaching material in schools